Striga Biocontrol on a Toothpick: A Readily Deployable and Inexpensive Method for Smallholder Farmers - Nzioki, Henry S.; Oyosi, Florence; Morris, Cindy E.; Kaya, Eylul; Pilgeram, Alice L.; Baker, Claire S.; Sands, David C. (Frontiers in Plant Science, 2016)
Striga hermonthica (witchweed) is a parasitic weed that attacks and significantly reduces the yields of maize, sorghum, millet, and sugarcane throughout sub-Saharan Africa. Low cost management methods such as hand weeding, short crop rotations, trap cropping, or conventional biocontrol have not been effective. Likewise, Striga-tolerant or herbicide-resistant maize cultivars are higher yielding, but are often beyond the economic means of sustenance farmers. The fungal pathogen, Fusarium oxysporum f.sp. strigae, has been the object of numerous studies to develop Striga biocontrol. Under experimental conditions this pathogen can reduce the incidence of Striga infestation but field use is not extensive, perhaps because it has not been sufficiently effective in restoring crop yield and reducing the soil Striga seed bank. Here we brought together Kenyan and US crop scientists with smallholder farmers to develop and validate an effective biocontrol strategy for management of Striga on smallholder farms. Key components of this research project were the following: (1) Development of a two-step method of fungal delivery, including laboratory coating of primary inoculum on toothpicks, followed by on-farm production of secondary field inoculum in boiled rice enabling delivery of vigorous, fresh inoculum directly to the seedbed; (2) Training of smallholder farmers (85% women), to produce the biocontrol agent and incorporate it into their maize plantings in Striga-infested soils and collect agronomic data. The field tests expanded from 30 smallholder farmers to a two-season, 500-farmer plot trial including paired plus and minus biocontrol plots with fertilizer and hybrid seed in both plots and; (3) Concerted selection of variants of the pathogen identified for enhanced virulence, as has been demonstrated in other host parasite systems were employed here on Striga via pathogen excretion of the amino acids L-leucine and L-tyrosine that are toxic to Striga but innocuous to maize. This overall strategy resulted in an average of >50% increased maize yield in the March to June rains season and >40% in the September to December rains season. Integration of this enhanced plant pathogen to Striga management in maize can significantly increase the maize yield of smallholder farmers in Kenya.